Design, synthesis and applications of novel soluble n-heteroacenes - Wang, Chengyuan (2015)
N-heteroacenes with the CH groups in the backbone of acenes replaced by N atoms are expected to own charming semiconducting properties and potential practical applications in organic electronics. The electron-deficient N-heteroacenes can be used as acceptor moieties in D-A molecules or n-type semiconductors depending on the application requirements. Although the researchers in all over the world are devoted to developing commercially available organic electronics, the study of organic memories, photovoltaics (OPVs) and field-effect transistors (OFETs) can still not stride out laboratory conditions, and the ultimate organic materials, which can satisfy all requirements for practical applications in the three types of devices are in high desire. Inspired by this gap, this dissertation focuses on design and synthesis of novel soluble N-heteroacenes and investigation of their applications in organic memories, OPVs and OFETs. For organic memories, the molecules have been designed based on two assumptions about multiple electron “traps” or multiple electrons intermolecular charge transfer, and accordingly, different electron-deficient N-heteroacene units are combined together to induce multiple electron “traps” or strong electron-deficient N-heteroacenes are utilized to accept multiple electrons. The memory devices have been fabricated and the corresponding switching behaviors, the ON/OFF ratios, the endurance and retention performance have been evaluated. Molecular calculation has been carried out to study the structure-property relationship. In summary, an efficient molecular designing strategy to approach rewritable, multilevel organic memory materials has been developed. For OPVs, the D-π-A structure molecules are designed with large conjugated N-heteroacene as acceptor moiety and linked to widely investigated donor units by π-bridges. The large conjugation of N-heteroacenes is expected to induce broad absorption and facilitate charge carriers’ transport. The typical BHJ architecture OPV devices have been fabricated and the corresponding PCE, Voc, Jsc, and FF are investigated. Morphology analysis of the organic films has been carried out to study the effect of molecular stacking on the device performance. In summary the as-designed molecule has showed PCE up to ~2%, which is expected to own better performance after structure modification. For OFETs, large conjugated N-heteroacenes with deep LUMO level lower than -4.0 eV has been designed. The single-crystal OFET devices have been fabricated and the corresponding transfer and output curves, VTH, ON/OFF ratios and field-effect mobility are investigated. Theoretical calculation has been conducted to study the ideal mobility of molecules and structure-property relationship. In summary a new family of N-heteroacenes have been developed for air-stable, high performance n-type OFETs.